A study of Korean drama and Indonesian teenager’s perception on images of South Korea as a potential tourist destination - Dita Dwi Maura Titania; Jony Oktavian Haryanto (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2022)
The popularity of Korean culture among teenagers around the world has made many teenagers, including Indonesian teenagers, affected by this culture. This Korean culture well known as Korean Wave or Hallyu. Korean Wave or Hallyu is a term to describe South Korean pop culture that has been successfully exported across the globe, including Indonesia. In Indonesia, Korean Wave or Hallyu products were introduced through the Korean television series called Korean drama. The objectives of this study are to determine how the teenagers in Indonesia perceive South Korean images as a destination that is seen in Korean dramas and could lead to the intention to visit South Korea in the future, to find out what are the impacts of watching Korean drama on consumer decision-making on Korean products and to find out whether watching Korean drama could increase the brand awareness towards a brand on Indonesian teenagers. This study uses qualitative methodology. Informants in this study were Indonesian teenagers range age 20-21 years old. Data collection for this study is obtained through interviews. By conducting this research, the researcher hopes to increase readers' insight into consumer decision-making that is influenced by the Korean Drama. The researcher hopes that this study may help future researchers who will conduct similar research from different aspects.